Violent Acts as a Factor, Influencing the Qualification of Certain Offenses (Article 6.1.1 of the Code of the Russian Federation on Administrative Offences and Article 156 of the Criminal Code of the Russian Federation) - A. V. Ravnyushkin (Сибирское юридическое обозрение, 2022)
Violent actions are a component of the objective side of many offenses. They serve as a factor influencing the qualification of offenses that have not received proper scientific and legislative assessment, which is clearly reflected in the current structures of offenses under Art. 6.1.1 of the Code of the Russian Federation on Administrative Offences “Battery” and Art. 156 of the Criminal Code of the Russian Federation “Failure to fulfill the obligations of raising a minor.” In the first case, there are a number of debatable issues related to the definition of the object of the specified administrative offense, the objective side, as well as the personality of the minor victim. In the second case, despite its legal significance (in terms of consequences), such a negative factor as ill-treatment of minors did not receive proper conceptual development in Russian legislation. The legislator and the Plenum of the Supreme Court of the Russian Federation treat it as an evaluative concept, which is true from the point of view of legal technique, but from the point of view of law enforcement, it raises the question of what signs should indicate the presence of this circumstance? The purpose of the study is to determine the structural parts of violent acts that form the objective side of the offenses under consideration. Achieving the goal is possible by solving the following tasks: to determine the properties of violent acts that indicate cruelty to minors in case of failure to fulfill the duties of raising minors (on the example of repeated administrative offenses under Art. 6.1.1 "Battery"); develop a legal assessment of such a circumstance as the commission of violent acts in family and domestic conflicts (in particular, beatings) in the presence of minors; submit proposals for improving Russian legislation on the issues under consideration. The methodological basis of the study was a dialectical approach to the scientific knowledge of social relations in which violence (beatings) and cruel treatment of minors is committed; comparative analysis, synthesis of the results obtained in the course of the study, which made it possible to substantiate the need for the development of acts of state bodies. Among the special methods used in the study are the method of studying normative legal acts and documents, the empirical method, the method of processing and analyzing data, and their generalization. As a toga of the study, some acts are proposed for discussion that may indicate ill-treatment of minors and either be an integral part of it, or serve to distinguish between administrative offenses under Art. 6.1.1 of the Code of the Russian Federation on Administrative Offences from crimes under Art. 156 of the Criminal Code of the Russian Federation. Violent actions that characterize the cruel treatment of a minor in case of failure to fulfill the duties of raising minors include those that express heartlessness, ruthlessness, cause suffering to a minor by inflicting bodily harm, beatings, committing other violent acts, threats, etc. It is proposed in Art. 6.1.1 of the Code of the Russian Federation on Administrative Offences to add a part 2 (qualified composition), indicating in it the same actions as in part 1, but committed against a minor and (or) against an adult in the presence of a minor, providing for a more severe punishment.